Programmed cell death associated with the formation of schizo-lysigenous aerenchyma in Nelumbo nucifera root - Xie, Qinmi; Hou, Hui; Yan, Peixuan; Zhang, Haiying; Lv, Yingze; Li, Xuebin; Chen, Lin; Pang, Danbo; Hu, Yang; Ni, Xilu (Frontiers in Plant Science, 2022)
Aerenchyma formation in Nelumbo nucifera (N. nucifera) root is an adaptive trait to the aquatic environment in long-term evolution. In this study, light microscopy, electron microscopy, and molecular biology techniques were used to study the process of the aerenchyma development and cytological events in N. nucifera root and the dynamic changes of aerenchyma formation under the treatment of exogenous 21% oxygen, ethylene (ET), and ET synthesis inhibitor 1-methylcyclopropene (1-MCP). The results showed that programmed cell death (PCD) occurred during the aerenchyma formation in N. nucifera root. Plasmalemma invagination and vacuole membrane rupture appeared in the early stage, followed by nuclear deformation, chromatin condensation and marginalization, and TUNEL detection was positive at this time. In the middle stage of the aerenchyma development, cytoplasmic degradation and many vesicles appeared in the cytoplasm, and organelles began to degrade. Then the plasma membrane began to degrade, and the degradation of the cell wall was the last PCD step. After 21% oxygen was continuously filled in the rhizosphere environment of N. nucifera roots, the area of aerenchyma in N. nucifera roots was smaller than that in the control group. Moreover, ET induced the earlier occurrence of aerenchyma in N. nucifera root, but also, the area of aerenchyma became larger than that of the control. On the contrary, 1-MCP inhibited the occurrence of aerenchyma to some extent. Therefore, the formation of aerenchyma in N. nucifera root resulted from PCD, and its formation mode was lysigenous. A hypoxic environment could induce aerenchyma formation in plants. ET signal was involved in aerenchyma formation in N. nucifera root and had a positive regulatory effect. This study provides relevant data on the formation mechanism of plant aerenchyma and the cytological basis for exploring the regulation mechanism of plant aerenchyma formation.